Multi-stage population models applied to insect dynamics - Benedito, Antone dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
This thesis presents two manuscripts previously sent to publication in scientific journals. In the first manuscript, a delay differential equation model is developed to study the dynamics of two Aedes aegypti mosquito populations: infected by the intracellular bacteria Wolbachia and non-infected (wild) individuals. All the steady states of the system are determined, namely extinction of both populations, extinction of the infected population and persistence of the non-infected one, and coexistence. Their local stability is analyzed, including Hopf bifurcation, which promotes periodic solutions around the nontrivial equilibrium points. Finally, one investigates the global asymptotic stability of the trivial solution. In the second manuscript, after rearing soybean looper Chrysodeixis includens in laboratory conditions, thermal requirements for this insect-pest are estimated, from linear and nonlinear regression models, as well as the intrinsic growth rate. This parameter depends on the life-history traits and can provide a measure of population viability of the species.
Multi-stage population models applied to insect dynamics
Keywords: Insects; Aedes aegypti; Delay differential equations; Wolbachia; Chrysodeixis; Soybean looper; Nonlinear regression; Intrinsic growth rate; Thermal requirements